2021
DOI: 10.1002/jmv.27160
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of ACE (I/D) and ACE2 receptor gene (Rs2106809, Rs2285666) are not related to the clinical course of COVID‐19: A case study

Abstract: Coronavirus disease 2019 (COVID‐19) is an infectious disease, and the reason behind the currently ongoing pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Angiotensin‐converting enzyme (ACE2) has been recognized as the specific receptor of the SARS‐CoV‐2 virus. Although the possible effect of ACE2 gene polymorphism remains unknown, human ACE2 receptor expression influences SARS‐CoV‐2 susceptibility and COVID‐19 disease outcome. In this study, we aimed to investigate the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 33 publications
11
80
3
1
Order By: Relevance
“…Conversely, our results showed no significant association of this variant with COVID-19 outcomes, but we found a significant association with hypertension that could be an indirect effect of COVID-19 complications (see Supplementary Material ). In agreement with our results, Karakas et al reported that I/D was not associated with the severity of COVID-19 infection in Turkey populations ( 33 ). Nevertheless, it is important to point out that the D/D genotype of ACE gene has a role on the renin–angiotensin system, by increasing ACE levels and angiotensin-inactivating AT-1 receptor, and downstream pathophysiological effects.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, our results showed no significant association of this variant with COVID-19 outcomes, but we found a significant association with hypertension that could be an indirect effect of COVID-19 complications (see Supplementary Material ). In agreement with our results, Karakas et al reported that I/D was not associated with the severity of COVID-19 infection in Turkey populations ( 33 ). Nevertheless, it is important to point out that the D/D genotype of ACE gene has a role on the renin–angiotensin system, by increasing ACE levels and angiotensin-inactivating AT-1 receptor, and downstream pathophysiological effects.…”
Section: Discussionsupporting
confidence: 93%
“…32%; p = 0.049) ( Gómez et al, 2020 ). The two polymorphisms were also not associated with COVID-19 severity in Turkish patients ( Karakaş Çelik et al, 2021 ). However, frequency of rs4646994 II genotype was reported to be significantly increased in Czech patients with symptomatic COVID-19 compared to controls (26.2 vs .…”
Section: Discussionmentioning
confidence: 95%
“…The ACE2 gene (Gene ID: Gene ID: 59272) is located in the short arm of human X chromosome (Xp22.2) and consists of 22 exons ( https://www.ncbi.nlm.nih.gov/gene/59272 ). Several SNPs of the gene, for instance rs4240157, rs4646155, and rs4830542, have been associated with the risk of hypertension, but recent studies in COVID-19 have focused on SNP rs2285666 ( Cafiero et al, 2021 ; Devaux et al, 2020 ; Gómez et al, 2020 ; Karakaş Çelik et al, 2021 ; Pouladi and Abdolahi, 2021 ; Singh et al, 2021 ). Although these studies proposed a role for SNPs rs4646994 and rs2285666 in COVID-19 susceptibility and/or disease severity, the evidence has not been conclusive as some findings have not been replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, controversial results have been published on the role of different ACE2 SNPs in COVID-19 disease. Karakaş et al (2021) failed to show any association between rs2106809 and rs2285666 and the clinical course of COVID-19 in a cohort of 155 patients [35]. On the other hand, Srivastava et al (2020) published a positive correlation between rs2285666 and a lower infection rate as well as case-fatality rate among Indian populations [19].…”
Section: Plos Onementioning
confidence: 99%